(untitled) (Journal of Surgical Sciences, 2019)
A 60-year-old man presented with malignant melanoma on left heel with left inguinal lymphnode metastasis. He developed right hemiparesis on the 3rd POD of wide local excision of anulcerated lesion of the left sole. CT scan showed multiple cerebral metastasis in the bothparietal lobes. No neurological features also manifested before operation of the primary lesion. Journal of Surgical Sciences (2016) Vol. 20 (1) : 32-33